Cultivated bacteria from the sub-ice algae-bacterial communities of Lake Baikal - M. V. Bashenkhaeva; Yu. R. Zakharova (Acta Biologica Sibirica, 2017)
A collection of pure cultures isolated from the sub-ice algae-bacterial communities inhabiting the lower ice surface of Lake Baikal was obtained. The differences in morphology of the cultured bacteria and their enzymatic activities were revealed by the methods of classical microbiology. The taxonomic affiliation of several cultures was determined by the 16S rRNA gene sequencing. They belong to the genera Pseudomonas putida, P. psychrophila, Methylobacterium extorquens, Rhodococcus aerolatus, Brevundimonas aurantiaca, B. vesicularis, Sphingomonas subarctica, Roseomonas frigidaqua, and Janthinobacterium lividum. These taxa are adapted to low-temperature environments.